Postpartum Maternal Mental Health: Identification of Risk Factors and Holistic Intervention Approaches - Zakiyah; Irma Fitria; Sri Wahyuni; Grace Carol Sipasulta; Sirajul Muna (Miracle Journal Get Press, 2025)
Postpartum maternal mental health is a critical issue that directly affects maternal well-being and child development. Postpartum Depression (PPD) is the most common disorder, often accompanied by anxiety, stress, and other psychological problems that can hinder recovery, bonding, and parenting.Risk factors for postpartum mental health disorders include role adjustment stress, previous mental health history, childbirth complications, unplanned pregnancy, hormonal imbalance, limited social support, fatigue, and sleep disturbances. Identifying these factors is essential to guide prevention and intervention strategies. This study applies a qualitative review with thematic analysis of existing findings. Results highlight the effectiveness of holistic interventions, such as psychosocial support, cognitive behavioral therapy (CBT), mindfulness, prenatal and postnatal education, balanced nutrition for hormonal stability, and pharmacological treatment when necessary. Partner and family involvement also play a crucial role in maternal recovery.In conclusion, comprehensive and holistic approaches are needed to address postpartum maternal mental health, ensuring optimal physical and emotional outcomes for mothers and children.